Twitter reacts to absence of women on Wikipedia: a mixed-methods analysis of #VisibleWikiWomen campaign. Issue 2 (11th March 2022) - Gupta, Sneh; Trehan, Kulveen
Abstract: Digital gender divide (DGD) is visible in access, participation, representation, and biases against women embedded in Wikipedia, the largest digital reservoir of co-created content. This article examined the content of #VisibleWikiWomen, a global digital advocacy campaign aimed at encouraging inclusion of women voices in the global technology conversation and improving digital sustainability of feminist data on Wikipedia. In a mixed-methods study, Sentiment Analysis followed by a Feminist Critical Discourse Analysis of the campaign tweets reveals how digital gender divide manifested in the public response. An overwhelming majority of tweets expressed positive sentiment towards the objective of the campaign. An inductive reading of the coded tweets ( n  = 1067) generated five themes: Feminist Activism, Invisibility & Marginalization of Women, Technology for Women Empowerment, Gendered Knowledge Inequity, and Power Dynamics in the Digital Sphere. Twitter discourse presented many agitated digital users calling out the epistemic injustice on Wikipedia that goes beyond the invisibility of women. Their tweets reveal that they want an equal social platform inclusive of women of color and varied identities currently absent in the Wikipedia universe. Extracting ideas, values, and themes from new media campaigns holds unparalleled potential in the diffusion of interventions and messages on a larger scale.